Di-(2-ethylhexyl) phthalate exposure induces liver injury by promoting ferroptosis via downregulation of GPX4 in pregnant mice - Zhang, Fan; Zhen, Hualong; Cheng, Hengshun; Hu, Fengying; Jia, Yunfei; Huang, Binbin; Jiang, Minmin (Frontiers in Cell and Developmental Biology, 2022)
Abstract As one kind of endocrine disrupting chemical, di-(2-ethylhexyl) phthalate (DEHP) has been reported to cause liver dysfunction in epidemiological and experimental studies. Abnormal liver function in pregnancy is associated with adverse maternal and perinatal outcomes. Few studies have investigated the potential effect of gestational DEHP exposure on the liver in pregnant mice, and the underlying mechanisms remain unclear. In the present study, pregnant ICR mice were exposed to doses (0, 500, 1000 mg/kg/day) of DEHP in the presence or absence of 5 mg/kg/day ferrostatin-1 (Fer-1, ferroptosis inhibitor) by oral gavage from gestation day 4 to day 18. HepG2 cells were exposed to different doses of monoethylhexyl phthalate (MEHP, a major metabolite of DEHP) in vitro. Hepatic function and pathologic changes were observed. Oxidative stress, iron metabolism, and ferroptosis-related indicators and genes were evaluated both in vivo and in vitro. The results showed that gestational DEHP exposure induced disordered liver function and hepatocyte morphology changes in pregnant mice, along with increased malondialdehyde (MDA) and Fe2+ content and decreased glutathione (GSH) levels. The expression levels of the selected ferroptosis-related genes Slc7a11, Gpx4, and Nfr2 were significantly decreased, and Ptgs2 and Lpcat3 were significantly increased. Notably, Fer-1 attenuated DEHP-induced liver injury and ferroptosis. Furthermore, MEHP exhibited a synergistic effect with RSL3 (a GPX4 inhibitor) in promoting ferroptosis in vitro. Taken together, the results demonstrated that DEHP induced liver injury and ferroptosis in pregnant mice, probably by inhibiting the GPX4 pathway through lipid peroxidation and iron accumulation.